An Analysis of Teacher Motivational Changes from the Perspective of Activity Theory: The Cases of Indonesian English Teachers in Thailand - Rosari, Maria Dewi; Mbato, Concilianus Laos ((JELE) Journal Of English Language and Education, 2020)
In this research, the researchers explore the motivational fluctuation of Indonesian teachers teaching in Thailand from the perspective of Activity Theory. The researchers chose participants teaching in different provinces in Thailand and spending different length of teaching there in order to provide more representative picture of the motivational fluctuation. The findings of the research indicated that the presence of teacher fellows and local community and students’ behavior functioned as the most significant elements for their teaching motivation. The teachers’ motivation levels fluctuated most significantly when they were exposed to those elements, which in AT Theory are called subject and community. The other four AT Theory elements, namely object, mediational tools, rules, and division of labor, although gave influences to the teachers’ motivation, were the least likely to be as crucial as the previous two. School administrators and or academic supervisors could benefit from the findings of this study by making sure that the crucial elements of teacher motivation are well and positively maintained in the environment of their institutions; so that teachers could perform their jobs effectively and thus the school’s performances gradually increases.